Feasibility Analysis of Kasoami's Business in The Home Industry in Wundumbatu Sub-District, Poasia Sub-District Kendari City - Amin, Haidir; I Wayan; Sasmita, Farrah; Harudin, La Harudin; Panga, La Panga; Rahman, Seni; Sri Wiyati Mahrani (International Journal of Management and Education in Human Development, 2022)
Kasoami is cassava root half processed by steaming treatment. Kasoami has functional and economic value. This study aims to determine the feasibility of the cassava business with the method used the Benefit Cost Ratio of the cassava processing business and Net Present Value, Internal Rate of Return, Payback Period, and Break Event Point for the cassava business. The analysis results of the B/C Ratio value of the cassava business are 1.91, which means that the cassava business is feasible to develop because it has a B/C Ratio value ≥ 1. The NPV value analysis is Rp. 109,430,115. The NPV value is greater than zero, so based on the NPV criteria, the kasoami business is feasible. The IRR value of the kasoami business is 22.9%, and the IRR value is greater than the discount rate used, which is 6%. So, the development of the Kasoami business deserves to be developed. The Payback Period (PBP) value for the development of the kasoami business is 0.5 years (6 months). This value indicates that all investment costs invested in the cassava processing business development plan will be returned in the 6th-month maximum. BEP (Break Event Point) is a state of not making a profit but also not suffering from a loss. The calculation results for cassava production BEP is 1,569 kg, and the BEP cassava price is IDR 8,368/kg. The five investment feasibility criteria make the development of the Kasoami business feasible to run financially.